Temperature and Biodiversity Regulate the Robustness of Plant–Microbe Networks in Natural Forests at Large Scale - Kai Feng; Qing He; Xi Peng; Xingsheng Yang; Xiongfeng Du; Ziyan Wei; Shang Wang; Xiao Zou; Yuguang Zhang; Ye Deng (Global Change Biology, 2025)
The latitudinal diversity gradient (LDG) is one of the general ecological patterns and has been extensively studied in plant and microbial communities. However, whether plant–microbe networks follow latitudinal trends and the underlying mechanisms driving such patterns remain largely unknown. In this study, we used an ecological survey dataset with simultaneously investigated plant species and microbial data from 26 forests at a continental scale and constructed the plant–microbe networks for each forest across the latitude gradients. We observed clear latitudinal patterns in plant–microbe networks, consistent with the LDG. Specifically, both the richness of networked species and the nestedness of the network architecture declined from tropical to temperate forests. Moreover, the plant‐level network robustness decreased with increasing latitude, and positive biodiversity‐robustness relationships were observed for plants and microbes. Mean annual temperature (MAT) was the most important factor for the observed latitudinal patterns, especially for plant–microbe network stability, evidenced by the robustness index. Additionally, MAT had a stronger effect on plant robustness than soil pH, primarily through its influence on plant diversity. Overall, this study demonstrated the latitudinal distribution patterns of the plant–microbe networks in natural forests and highlighted the positive relationship between biodiversity and robustness through plant–microbe interaction processes.